2011
DOI: 10.2217/nnm.11.142
|View full text |Cite
|
Sign up to set email alerts
|

Design of Self-Assembling Peptides and Their Biomedical Applications

Abstract: Lecithin-chitosan nanoparticles are a promising carrier for topical delivery of quercetin.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
46
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 107 publications
(47 citation statements)
references
References 83 publications
1
46
0
Order By: Relevance
“…It was well documented that SAPs rarely showed toxicity and immune response in various cell and animal experiments because they were prepared from natural amino acids. 12,13 Our results also indicated that cationic SAP was a biocompatible nanomaterial to deliver bioactive cargos to β-cells.…”
Section: Discussionsupporting
confidence: 55%
See 3 more Smart Citations
“…It was well documented that SAPs rarely showed toxicity and immune response in various cell and animal experiments because they were prepared from natural amino acids. 12,13 Our results also indicated that cationic SAP was a biocompatible nanomaterial to deliver bioactive cargos to β-cells.…”
Section: Discussionsupporting
confidence: 55%
“…2,3 SAP could serve as a flexible platform to deliver various chemical drugs and bioactive proteins. 12,15,16 In this study, we fabricated a cationic SAP/ Hep hybrid gel to deliver HGF and evaluated its protective effect on β-cell in transplantation. KLD12 is an ionic-complementary peptide that contains positively charged lysines and negatively charged aspartic acids, and the net charge is zero.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…[13][14][15] Several wellstudied materials have been developed into clinically available formulations, such as Abraxane ® and Doxil ® . 16,17 At the same time, a category of self-assembling peptides as novel nanomaterials has emerged in the past decade with advanced properties in 18,19 Based on their chemical structures, selfassembling peptides could form different nanostructures including nanoparticles, nanotubes, and nanofibers, which are also potential carriers for drug delivery. [20][21][22][23][24][25][26] It has been demonstrated that nanostructures with a high aspect ratio are advantageous as drug carriers; 27,28 however, on the other hand, their drug loading capacity (LC) is usually very low, 24,29 which has hampered the development of a drug delivery system based on these nanomaterials.…”
Section: Introductionmentioning
confidence: 99%